Induction mechanism of ferroptosis: A novel therapeutic target in lung disease - Pan, Lingyu; Gong, Chunxia; Sun, Yehong; Jiang, Yeke; Duan, Xianchun; Han, Yanquan; Wang, Yongzhong (Frontiers in Pharmacology, 2022)
Ferroptosis is a newly discovered form of non-apoptotic regulatory cell death driven by iron-dependent lipid peroxidation. Ferroptosis significantly differs from other forms of cell death in terms of biochemistry, genetics, and morphology. Ferroptosis affects many metabolic processes in the body, resulting in disruption of homeostasis, and is related to many types of lung disease. Although current research on ferroptosis remains in the early stage, existing studies have confirmed that ferroptosis is regulated by a variety of genes, mainly involving changes in genes involved in iron homeostasis and lipid peroxidation metabolism. Furthermore, the mechanism of ferroptosis is complex. This review summarizes the confirmed mechanisms that can cause ferroptosis, including activation of glutathione peroxidase 4, synthesis of glutathione, accumulation of reactive oxygen species, and the influence of ferrous ions and p53 proteins. In recent years, the mechanism of ferroptosis in the occurrence and development of many diseases has been studied; the occurrence of ferroptosis will produce an inflammatory storm, and most of the inducing factors and pathological manifestations of lung diseases are also inflammatory reactions. Therefore, we believe that the association between ferroptosis and lung disease deserves further study. This article aims to help readers to better understand the mechanism of ferroptosis, provide new ideas and targets for the treatment of lung diseases, and point out the direction for the development of new targeted drugs for the clinical treatment of lung diseases.